Novel Diagnostic approach for tuberculosis diagnosis - Milovic, Ana (Division of Medical Microbiology, 2014)
There is a clear need for a rapid, inexpensive point-of-care diagnostic test for tuberculosis (TB). The aim of this study was to analyze the performance of a novel rapid diagnostic test for TB, GeneXpert MTB/RIF, in symptomatic adults and to compare it to other commercially available nucleic acid amplification assays and to standard microbiological smear and culture. The GeneXpert system performs real time, nested PCR from sputum and provides a result within two hours of sampling. The result includes a semi-quantitative assessment of bacillary load in the sample and simultaneously detects rifampicin resistance. This study was part of a cross-sectional, multi-centre clinical trial. The Cape Town component of this study was conducted at three sites, one hospital based and other two community clinics, all with high TB/HIV coinfection rate. Among 43.2% of patients diagnosed with TB during the evaluation study, GeneXpert detected TB in 95.5% of all culture positive cases. In smear positive patients, sensitivity was 99.0% and in smear-negative, culture positive patients, 86.1%. Specificity in patients who were culture negative and clinically diagnosed as non-TB after follow up was 98.4%. Sensitivity and specificity of GeneXpert in detecting rifampicin resistance was 100% comparing to phenotypically detected drug resistance. GeneXpert is a highly promising novel tool for the rapid diagnosis of adult TB. Future studies are needed to establish the performance and impact of GeneXpert when performed at the level of the microscopy centre.